The slipped disc: a guide to the identification of shell disc-beads - Ward, V.; Maggs, T. (Southern African Humanities, 2021)
Excavations of the past two decades in Natal have produced disc-beads made of a variety of materials. Because these materials have not been adequately examined and described, some disc-beads have been incorrectly identified which may lead to incorrect archaeological interpretation. An aid towards correct identification is presented. To cite this article: Ward, V. & Maggs, T. 1988. The slipped disc: a guide to the identification of shell disc-beads. Annals of the Natal Museum 29 (2): 407-16.